Double prey a Posadas County mystery - Havill, Steven (Scottsdale, AZ : Poisoned Pen Press, 2011)
A boy goes missing and is found dead in an arroyo, apparently killed in an ATV accident. But the discovery he made moments before he was killed is puzzling... and takes deputies back to a five year old killing and has them looking for a murderer too close to home.
Keywords: Reyes-Guzman, Estelle (Fictitious character); Policewomen; Murder -- Investigation; New Mexico; Mystery fiction